Comparison of the Effectiveness of Lyophilized Amniotic Membranes in the Partial Thickness Wound Healing Process in Mus musculus - Srigunda Arisya Fadilla; Rizki Rahmadian; Benni Raymond (HM Publisher, 2023)
Background: Currently, tulle or gentamicin ointment is generally used to prevent wound infections in wound care. Human amniotic membrane has been used in medical fields such as wound care. So far, there is no comparative evidence of the effectiveness of each ingredient. This study aimed to compare the effectiveness of lyophilized amniotic membrane, tulle, and 0.1% gentamicin ointment in the wound healing process. partial thickness on Mus musculus clinically and histologically. Methods: This type of research is experimental with a post-test-only control group design. There were 24 rats divided into each group. This research was conducted at the anatomical pathology laboratory, Faculty of Medicine, Universitas Andalas, and INA lab in July - September 2023 using rats (Mus musculus), which were divided into 3 treatment groups and one control group. Results: Clinically, lyophilized amniotic membrane, 0.1% gentamicin ointment, and tulle provided better results than controls regarding erythema variables. Histologically, the results showed that the lyophilized amniotic membrane group had the thinnest epidermis and dermis, as well as better histological scores for granulation, fibroblasts, and collagen than the 0.1% gentamicin ointment, tulle, and control groups. In this study, significant differences in effectiveness were found in terms of erythema, skin thickness, granulation, fibroblast, and collagen histological scores, with better results in the lyophilized amniotic membrane group. Conclusion: Clinically, lyophilized amniotic membrane, tulle, and 0.1% gentamicin ointment were more effective than controls for wound treatment due to faster reduction in erythema. However, histologically, the lyophilized amniotic membrane was proven to be more effective than tulle, 0.1% gentamicin ointment, and control in terms of epidermis and dermis thickness, granulation level, fibroblasts, and collagen.